Эмоционально-оценочная лексика как результат семантического словообразования - Nikołajewa, Tatiana (Wydawnictwo Naukowe UAM, 2010)
In the article the system character of semantic transformation is proved on the material of emotional-estimated lexicon. The author confirms the position of Kazan linguistic school – a new meaning presumes a new self-functioning word. The investigator offers a scheme of interpretation of semantic derivatives in a specialized dictionary.
The emotional-evaluative vocabulary as a result of semantic derivation
Słownictwo emocjonalno-wartościujące jako wynik derywacji semantycznej